Paleoenvironmental Analysis and Rice Farming at the Huangshan Site, Central China - Hao Lu; Jun Chai; Jun-Cai Ma; Kun Liang (Heritage)
The Huangshan site in Nanyang, situated at the junction of the Nanyang Basin and the Jianghan Plain, represents a critical region for understanding the northward expansion of rice farming in China. Due to the scarcity of suitable organic material, the dating of the channel section at Huangshan relies primarily on cultural relics. By employing grain-size analysis, pollen analysis, and phytolith analysis on sediment samples from the site’s river section, we established a comprehensive framework of hydrology, climate, vegetation, and agricultural activities during the Yangshao to Qujialing periods (ca. 7000–4600 BP). The findings indicate a relative decline in temperature during the Yangshao period, followed by a return to warm and humid conditions during the Qujialing period, which coincided with the peak intensity of rice farming. The continuous expansion of rice farming at the Huangshan site during prehistoric times is likely linked to the northward spread of Qujialing culture. The large-scale production of rice not only provided an economic foundation for the growth of the Huangshan settlement but also facilitated its development into a regional hub for jade production and trade. This study offers new environmental archaeological insights into the interactions between the middle Yangtze River region and the Central Plains during the late Neolithic period.